Requirement Engineering in Component Selection - Gupta, Rashmi (My University, 2010)
In the COTS selection process, it is unavoidable to encounter mismatches between system requirements and COTS products’ capabilities. These mismatches are the result of the lacking COTS attributes or their overmatch with the system requirements. Many researchers have proposed various techniques to search and select COTS components. But only few have worked upon the handling of mismatches. These techniques have their own advantages and disadvantages. This thesis work proposes a COTS selection approach that aims at addressing COTS mismatches among COTS attributes and system requirements during the requirement engineering phase. In this process COTS evaluation, a core activity of COTS selection, is performed using the Goal Question Metrics (GQM) based Feature Analysis technique. GQM based Feature Analysis is an evaluation strategy used for measuring the compliance of the COTS capabilities with desired features using the formulated metrics. A case-study is used to illustrate this process and to discuss its feasibility.
M.E. (Software Engineering)
Keywords: Requirement Engineering; COTS Selection Techniques